The Research Methodology In Health Law - Maria Célia Delduque; Sandra Mara Campos Alves (Oswaldo Cruz Foundation, Health Law Program, 2015)
Legal research is usually limited to the field of analysis of doctrine and jurisprudence and also knowledge of legal-formal immediate sources. In the case of health law, whose central theme - health - has a great dynamism, requires not only the analysis of the wording of normative acts and judicial decisions. The facts lining these acts, permeated by biomedical, political, social, economic issues, among others, deserve analysis arising from other sources of knowledge and scientific methodology, combined with the hermeneutical method, are capable of conferring scientific approach more consistent with the complexity of the health law